(untitled) (Medicine Today, 2020)
Introduction: The aim of this study was to screening the Sensitivity of Alvarado score among the hospitalized suspected appendicitis patients at Dhaka National Medical College Hospital for determine the diagnostic accuracy. Materials and Methods: It was an observational type of descriptive study, conducted in the Dhaka National Medical College Hospital, Dhaka, during the study period of July 2015 to December 2015. The study was approved by the institutional ethical committee. Results: Most of the appendicitis patients belonged to the between 21-30 years which was 64 (32%). Male appendicitis patients (52%) are more than the female patients (48%). Majority of the patients (69%) complains pain occurs in the Right iliac fossa. The sensitivity of Alvarado scores was 81.60%, specificity 74.58%, accuracy 79.35%, positive and negative predictive values were 87.18% and 65.67% respectively. Conclusion: Alvarado score has more specificity. Medicine Today 2020 Vol.32(1): 45-47